Analyzing the Influence of Entrepreneurial Leadership on Organizational Performance in Emerging Markets - Yulianto Wibowo; Rizqi argo falah; Ivan Adhi prasetyantono (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
Entrepreneurial leadership has gained prominence as a critical factor influencing organizational performance, particularly in emerging markets. This study examines how entrepreneurial leadership impacts organizational outcomes within Indonesian companies. Using a mixed-method approach, data were collected through surveys and in-depth interviews with leaders and employees in various sectors. The results show a strong correlation between entrepreneurial leadership traits—such as innovation, risk-taking, and proactive behavior—and improved performance metrics. The paper discusses practical implications for fostering an entrepreneurial mindset within organizations to enhance resilience and competitive advantage in volatile markets.